2016
DOI: 10.1002/ajmg.a.37878
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular findings in 39 patients with KBG syndrome caused by deletion or mutation of ANKRD11

Abstract: KBG syndrome, due to ANKRD11 alteration is characterized by developmental delay, short stature, dysmorphic facial features, and skeletal anomalies. We report a clinical and molecular study of 39 patients affected by KBG syndrome. Among them, 19 were diagnosed after the detection of a 16q24.3 deletion encompassing the ANKRD11 gene by array CGH. In the 20 remaining patients, the clinical suspicion was confirmed by the identification of an ANKRD11 mutation by direct sequencing. We present arguments to modulate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
149
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(166 citation statements)
references
References 39 publications
14
149
2
1
Order By: Relevance
“…Additionally, this case also demonstrates the variability of the clinical manifestations of KBG syndrome, as any macrodontia in the proband was not noticeable enough to be recognized and associated with any syndrome diagnosis by any clinician, including medical geneticists, before the molecular diagnosis of the syndrome. This is consistent with the very recent suggestion that macrodontia should not be considered a “mandatory feature” of KBG syndrome (Goldenberg et al 2016). In addition, seizures are an often reported feature of KBG syndrome, found in up to 28% of patients (Skjei et al 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, this case also demonstrates the variability of the clinical manifestations of KBG syndrome, as any macrodontia in the proband was not noticeable enough to be recognized and associated with any syndrome diagnosis by any clinician, including medical geneticists, before the molecular diagnosis of the syndrome. This is consistent with the very recent suggestion that macrodontia should not be considered a “mandatory feature” of KBG syndrome (Goldenberg et al 2016). In addition, seizures are an often reported feature of KBG syndrome, found in up to 28% of patients (Skjei et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…More than 100 cases have now been reported (see Fig. 6; Ockeloen et al 2015; Goldenberg et al 2016); however, it is likely that KBG syndrome is underdiagnosed because dysmorphic features may be underreported, subtle, or even nonexistent, and cognitive delay can vary from mild to moderate (Crippa et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Two patients showed hematological abnormalities (one had a pancytopenia with bone marrow hypoplasia and the second had anemia and leukopenia). Only 1 patient was previously reported with acute myeloid leukemia [Goldenberg et al, 2016], and a role of ANKRD11 in cancer predisposition was proposed, but not confirmed [Neilsen et al, 2008;Lim et al, 2012]. The presence of thrombocytopenia was pointed out as a possible feature distinguishing between KBG syndrome and 16q24 microdeletion syndrome, where ANKRD11 flanking genes are also involved [Novara et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…The following patients have been previously reported in articles: #3 and #4, #8, #13, #14, #23, #26, and #51 …”
Section: Methodsmentioning
confidence: 99%